Bridging Potential in Friend Networks and Cognitive Function in Older Korean Americans. (March 2022) - Jang, Yuri; Kim, Jangmin; Yoon, Hyunwoo; Park, Nan Sook; Chiriboga, David A.
Objectives: To examine the associates of bridging potential in networks of friends and its impact on cognitive function in older Korean Americans. Methods: Data came from 308 participants in Central Florida who were part of the Study of Older Korean Americans (SOKA). Using data from a name generator of three close friends in local Korean communities, non-overlapping networks were quantified for bridging potential. Linear regression models for bridging potential and cognitive function were examined. Results: Bridging potential was greater among those with stronger social ties with friends in general and higher levels of activity engagement. The direct benefit of bridging potential on cognitive function was also confirmed. In addition, bridging potential was found to mediate the effect of social ties with friends on cognitive function. Discussion: Findings underscore the interconnectedness of older immigrants' social and cognitive function and shed light on interventions.